2011
DOI: 10.1186/1751-0759-5-2
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of the Japanese version of the Levels of Emotional Awareness Scale (LEAS-J)

Abstract: BackgroundThe Levels of Emotional Awareness Scale (LEAS) was developed to assess five levels of emotional awareness: bodily sensations, action tendencies, single emotions, blends of emotion, and combinations of blends. It is a paper and pencil performance questionnaire that presents 20 emotion-evoking scenes. We developed a Japanese version of the LEAS (LEAS-J), and its reliability and validity were examined.MethodsThe LEAS-J level was independently assessed by two researchers who scored each response accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
4
24
0
1
Order By: Relevance
“…In a larger sample (N 5 380), alpha coefficients were high for the Self (α 5 .84), Other (α 5 .83), and total (α 5 .88) scores (Lane et al, 1996). Similar Cronbach alpha coefficients (Self 5 .82, Other 5 .77, total 5 .83) were reported for the LEAS-J subscales (Igarashi et al, 2011).…”
Section: Internal Consistencysupporting
confidence: 52%
See 1 more Smart Citation
“…In a larger sample (N 5 380), alpha coefficients were high for the Self (α 5 .84), Other (α 5 .83), and total (α 5 .88) scores (Lane et al, 1996). Similar Cronbach alpha coefficients (Self 5 .82, Other 5 .77, total 5 .83) were reported for the LEAS-J subscales (Igarashi et al, 2011).…”
Section: Internal Consistencysupporting
confidence: 52%
“…In Lane et al (1996), inter-rater reliabilities were high for the Self (r 5 .98), Other (r 5 .91), and total (r 5 .92) scores. Similarly, Igarashi et al (2011) reported acceptable levels of inter-rater reliability (Self 5 .88, Other 5 .87, total 5 .90).…”
Section: Inter-ratermentioning
confidence: 89%
“…DDI and DDF are considered to be ‘affective’ facets of alexithymia, but EOT is less correlated with the other two [16,70] and is thought to reflect more the ‘cognitive’ dimension of alexithymia [71,72]. Among the three TAS subscales, EOT is the only factor that has a significant (negative) correlation with the levels of emotional awareness scale (LEAS) [73,74]. It is quite noteworthy that EOT does not correlate with depression but correlates negatively with the degree of interoceptive awareness, which is scaled as accuracy in a heartbeat detection task [57].…”
Section: Discussionmentioning
confidence: 99%
“…The inter-rater reliability of LEAS is typically high, with several studies having a Cronbach alpha of 0.90 and over. The LEAS has also met certain demands for criterion validity since it correlates with for example empathy and psychological maturity (Lane et al, 1990 ; Bydlowski et al, 2002 ; Igarashi et al, 2011 ). The instrument has been found to predict emotion-related criteria, such as the ability to identify emotions and physiological brain activation in response to emotional stimuli (Lane et al, 1995 , 1996 ).…”
Section: Introductionmentioning
confidence: 99%